“Macroinvertebrados acuáticos como indicadores de calidad del agua en el estero el taco de la microcuenca baja del río Quevedo y su relación con los usos del suelo" - Macías Aldaz, Nataly Lilibeth (2020)
The use of macroinvertebrates as indicators of water quality has been used as a complement to the analysis of physicochemical parameters, due to them they fulfill important functions in the transformation of organic matter, and considered essential components in the functioning of the aquatic ecosystem. This research seeks to determine the aquatic macroinvertebrate communities present in the El Taco estuary and their relationship with land uses. During the months of December 2020 to February 2021, 27 samplings were carried out in 9 stations in three land uses (agricultural, forest, and grassland), for which the D-net with a 500 µm mesh was used, the specimens collected were identified up to gender level. The structure of the aquatic insect community was determined using the Shannon-Weaver diversity indices, Simpson dominance and Pielou richness using the PAST statistical program. A non-parametric similarity analysis (ANOSIM) was carried out to identify statistical differences in the similarity of aquatic macroinvertebrate genera between land uses and an analysis of variance or ANOVA to check differences in the calculated indices, and physicochemical parameters, in addition A redundancy analysis (RDA) was used to evaluate the degree of correlation between the abundance of aquatic macroinvertebrates and physicochemical parameters. To establish the water quality, the BMWP-Cr index was applied, and in the evaluation of the current state of the riverbank vegetation the riverbank forest quality indexes (QBR) and river habitat index (IHF). A total of 1425 individuals distributed in 10 orders, 14 families and 17 genera were collected. The results of the diversity indices showed that the site with the greatest dominance and diversity of macroinvertebrate genera was forest land use, while agricultural land use showed the greatest richness. The ANOSIM test showed that grassland land use presented statistical differences in the similarity of abundance of aquatic macroinvertebrate genera between land uses. The BMWP-Cr index showed that the forest soil presents water of excellent water quality, while the index (QBR) a good quality, something similar indicated the index (IHF) with moderate quality for the use of forest soil. Keywords: Water quality, BMWP-Cr index, index (IHF), index (QBR)